Bridging Traditions: How Eastern and Western Architectural Practices Collaborate for Sustainable Housing - Raimond Vool (Institute for Research and Community Services Udayana University, 2026)
This article explores how Eastern and Western architectural practices can collaborate to create sustainable housing solutions, addressing the challenges posed by globalisation while promoting a balance between cultural values and ecological needs. Through the analysis of case studies from Estonia, Bali and West Africa, the paper examines how local knowledge can be integrated with modern technologies. The focus is on the use of local materials, climate responsive design, and energy efficiency throughout the whole process. The findings suggest that combining traditional architectural practices with global knowledge offers a pathway to sustainable housing that respects cultural identity and addresses ecological challenges. The study highlights how cross-cultural collaboration can foster innovative, sustainable architecture that meets both global and local needs.